(untitled) (SMC Journal Shadananda Multiple Campus, 2026)
Higher education in Nepal continues to be dominated by lecture-based, examination oriented teaching practices, which limit student engagement, critical thinking, and the skills required in contemporary learning contexts. This study argues that improving teaching quality and learning outcomes in Nepalese community campuses requires a shift toward student-centered learning grounded in human development principles. Adopting a qualitative and quantitative research design, the study draws on document analysis of relevant literature, review of faculty development initiatives at Tribhuvan University, analysis of digital pedagogy training programs offered by the Inter-University Centre for Teacher Education (IUCTE), and small-scale empirical evidence collected from selected community campuses through classroom observations and informal faculty consultations. The data were thematically analyzed to identify prevailing pedagogical practices and emerging instructional shifts. The findings reveal a persistent gap between pedagogical aspirations and classroom realities, with continued heavy reliance on lecture-based instruction despite increased awareness of student-centered approaches. The study demonstrates that student-centered pedagogy, supported by productive, digital, and TPACK-based pedagogies, can be implemented through consistent classroom level practices even in low-resource contexts. The study concludes that meaningful transformation in Nepalese community campuses depends on understanding learners and designing pedagogy that integrates content, pedagogy, and technology in context-sensitive and sustainable ways.